Grounding the Principles of Islamic Communication in Organizational Culture: A Case Study of State Islamic Higher Education Institutions - Rais Harahap, Amin; Abdullah, Abdullah (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2025)
This study aims to analyze the implementation of Islamic communication principles in the organizational culture of State Islamic Religious Higher Education (PTKIN), identify supporting and inhibiting factors, and examine their implications for organizational performance. The research method uses the Systematic Literature Review (SLR) approach to 25 selected scientific articles relevant to the topic of Islamic communication and PTKIN organizational management. The results of the study indicate that the implementation of Islamic communication in the PTKIN environment is integrated into five main principles: sidq (honesty), amanah (responsibility), syura (deliberation), adab (communication ethics), and hikmah (wisdom). These five principles are applied in the decision-making process, conflict management, interpersonal relationship development, and institutional governance. Supporting factors for implementation include a strong basis for organizational spirituality, Islamic visionary leadership, participatory organizational structure, and strengthening values ​​through academic curriculum. The inhibiting factors include resistance to organizational culture, lack of Islamic managerial training, dualism of management culture, and differences in perception between generations. Empirically, the application of Islamic communication has implications for increasing the effectiveness of governance, academic productivity, institutional reputation, and institutional stability of PTKIN in facing the dynamics of globalization of Islamic higher education.